Integration of internally displaced persons of Ukraine: realities, problems, perspectives - Niemets, Liudmyla Mykolaivna; Husieva, Nataliia Volodymyrivna; Pohrebskyi, Taras Heorhiiovych; Bartosh, Oksana Volodymyrivna; Lohvynova, Maryna Oleksandrivna (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2020)
Purpose. The article discusses the realities, problems and perspectives of internally displaced persons in Ukraine. The aim of the study is to justify the realities, problems and possible solutions to the problems of integration of Ukrainian IDPs into local communities.Scientific novelty. The article discusses theoretical and methodological approaches to understanding the adaptation and integration of IDPs, forms of integration, the category of interaction between forced migrants and the local population. The level of integration of IDPs into local communities in Ukraine has been investigated.Results. Self-assessment of IDPs for their full integration into local communities as of December 2018 is 50%. The self-assessment of IDPs of their integration into local societies by regions of Ukraine has been analyzed. The most integrated are the migrants of the southern, central and northern regions (Mykolaiv, Kherson, Kirovohrad, Poltava, Cherkasy, Sumy) – 70%, the least integrated IDPs in the eastern regions (Luhansk, Donetsk) – 43%.The dynamics of self-assessment of IDPs of their integration into local societies was analyzed during March 2017 – December in 2018 and it is certain that during 2018 the self-assessment of full integration of IDPs tended to increase (increased from 38% to 50%). An objective assessment of the integration of IDPs into local societies, where the majority of IDPs (63%) are partially integrated, is presented. The dynamics of assessing the integration of IDPs into local societies during 2017-2018 has been studied. and it was found that the level of full integration in 2018 was almost 2 times less than in 2017 (24-27% versus 45-58%).The conditions for successful adaptation of IDPs are defined, the main ones being housing (87%), permanent income (77%) and employment (48%). The level of trust of IDPs to the local population in the current places of residence of IDPs, the frequency of IDPs' requests to local residents for help in everyday life, the level of belonging of IDPs to the society in their current and past place of residence.Problems of integration of IDPs are identified. The biggest obstacle to attracting IDPs into the life of the territorial community is the lack of own housing, the problem of obtaining social services and the problem of employment. For successful integration of IDPs into host communities, a number of activities are proposed, among which are the formation and implementation of organizational and management principles for the effective integration of IDPs, the restructuring of social cohesion, the strengthening of socio-economic security and resilience of host societies to IDPs, the development of regional (local) programs and plans, taking into account the needs of IDPs and others.Practical significance. The results of this study can be used by the Ukrainian authorities at the state and regional levels to solve the problems of IDPs in Ukraine.